Optimization of Fermentation Conditions Required for Exopolysaccharide (EPS) Production by Bacillus altitudinis Strain EPBAS.1 Obtained from Brewery Wastewater Sludge - Jacob, Idorenyin O.; Umoh, Veronica J.; Antia, Ukponobong E. (International Journal of Scientific Research in Biological Sciences, 2024)
Bacteria exopolysaccharides (EPS) are long-chain high-molecular weight polysaccharides synthesize in bacteria and exported into the external environment and their production is influenced by several key cultural and fermentation conditions, which this study aimed to determine the optimum specific for Bacillus altitudinis strain EPBAS.1 obtained from brewery wastewater sludge for maximal production. Brewery wastewater sludge samples were collected and screened for EPS-producing bacteria using standard microbiological methods. The isolates were grown in broth culture for 48h, centrifuged at 4000 rpm for 30 minutes, the EPS extracted by ethanol precipitation to determine its yield, and the best EPS-producer identified molecularly and used for optimization study using one-factor at a time method. A total of 85 bacterial isolates were screened, 29 showed EPS production ability, while isolate EPBS.1 produced statistically (P<0.05) higher quantity (0.58±0.04g/100ml) of EPS, and was identified to the species level as Bacillus altitudinis strain EPBAS.1. From the optimization study, higher EPS yield (0.65±0.03g/100ml) was obtained with sucrose than other carbon sources. Organic nitrogen, with yeast extract as the most preferred, gave higher yield (0.68±0.01g/100ml) than inorganic nitrogen. pH, temperature, incubation period, inoculum size, and NaCl2 concentration gave optimal EPS yields at 7.0 (0.66±0.01g/100ml), 35oC (0.72±0.03g/100ml), 72h (0.69±0.01g/100ml), 4% (0.74±0.02g/100ml), and 5% (0.68±0.01g/100ml), respectively. The EPS extracts showed higher total carbohydrate (68.5±0.10%) than protein (16.2±0.31%) contents. Hence, the study reveals the optimal EPS production conditions for Bacillus altitudinis strain EPBAS.1 and recommends the use of sucrose, yeast extract, neutral pH, temperature at 35oC, 72h incubation time, 4% inoculum size, and 5% NaCl2 for optimal EPS production by the bacteria strain.